METHODS OF TEACHING ENGLISH THROUGH AUTHENTIC MATERIALS IN PRIMARY CLASSES (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This article focuses on effective, modern and innovative methods of English language teaching and the use of authentic materials to increase students' interest in language learning in elementary grades.